2000
DOI: 10.1038/sj.onc.1203204
|View full text |Cite
|
Sign up to set email alerts
|

Roles for the protein tyrosine phosphatase SHP-2 in cytoskeletal organization, cell adhesion and cell migration revealed by overexpression of a dominant negative mutant

Abstract: SHP-2, a SRC homology 2 domain-containing protein tyrosine phosphatase, mediates activation of Ras and mitogen-activated protein kinase by various mitogens and cell adhesion. Inhibition of endogenous SHP-2 by overexpression of a catalytically inactive (dominant negative) mutant in Chinese hamster ovary cells or Rat-1 ®broblasts has now been shown to induce a marked change in cell morphology (from elongated to less polarized) that is accompanied by substantial increases in the numbers of actin stress ®bers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 57 publications
4
67
0
Order By: Relevance
“…Mouse ®broblasts de®cient in functional SHP2 showed defects in cell migration and spreading on ®bronectin (Yu et al, 1998). However, expression of catalytically-inactive SHP2 in Rat-1 ®broblasts and CHO cells increased the rate of cell attachment to and spreading on ®bronectin (Inagaki et al, 2000). Therefore, the mechanism by which SHP2 regulates cell motility is not clear and may require a highly complex coordination of signals that are related to cell context.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse ®broblasts de®cient in functional SHP2 showed defects in cell migration and spreading on ®bronectin (Yu et al, 1998). However, expression of catalytically-inactive SHP2 in Rat-1 ®broblasts and CHO cells increased the rate of cell attachment to and spreading on ®bronectin (Inagaki et al, 2000). Therefore, the mechanism by which SHP2 regulates cell motility is not clear and may require a highly complex coordination of signals that are related to cell context.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous reports that showed that SHP2 plays a positive role in fibroblast motility and migration. [23][24][25][26] Thus, interference with SHP2 function might provide a means to inhibit cancer cell metastasis. Unexpectedly, we discovered that EGF can induce translocation of b-catenin to the nucleus in SHP2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that SHP2 suppresses cell adhesion and enhances motility. [23][24][25][26] We sough to investigate the significance of SHP2 inhibition on breast cancer cells motility and scattering. Initially, this possibility was tested by the monolayer wound-healing assay.…”
Section: Shp2mentioning
confidence: 99%
“…When overexpressed, the SHP-2 C459S (SHP-2 C/S) mutant inhibits endogenous SHP-2 function by dominantnegative inhibition of the catalytic activity of SHP-2 and/or trapping its substrates. This mutant has been widely used to study SHP-2 function in cell signaling (Bennett et al, 1996;Maegawa et al, 1999;Manes et al, 1999;Inagaki et al, 2000). We transduced primary BM cells with SHP-2 C/S.…”
Section: Il-3-elicited Signal Transduction In Shp-2 à/à Cells Is Impamentioning
confidence: 99%